Paliperidone-loaded nose to brain targeted NLCS: optimisation, evaluation, histopathology and pharmacokinetic estimation for schizophernia - Khedkar M.A.; Sharma V.; Anjum M.; Singh S.; Shah K.; Alam P.; Dewangan H.K. (My University, 2025)
Study was to develop a nanostructured-lipid-careers (NLCs) of paliperidone (PLP) for nose-to-brain targeting. NLCs was prepared by sonication, high-shear homogenisation method, and characterised their mean diameter, PDI, zeta-potential, morphology (by SEM, TEM and AFM), entrapment efficiency, drug loading, in vitro release, interaction study (by FTIR), and stability. Further, ex vivo permeation and ciliotoxicity performed in sheep nasal mucosa, and in vivo biodistribution/pharmacokinetic was performed in rats for schizophernia. Developed NLCs showed spherical and clearly 3-dimentinal structure with 129 ± 2.7 nm mean diameter, 0.304 ± 0.003 PDI, −7.61 ± 0.56 mV zeta-potential, 58.16 ± 0.17% entrapment efficiency, 65.8 ± 2% drug loading and 74.32 ± 0.003% release in 12 h, followed by Higuchi model. Ex vivo study showed NLCs have three times higher permeation, compare to pure drug (around 71.50.32% in 6 h) and 3.98 g/cm2/h steady sate flux. The blood/brain ratio given by intranasally have higher compare to IV route, and 94.53 ± 21.45% drug targeting efficiency in brain. In conclusion, NLCs have easily crossed BBB, higher drug delivery and effective for schizophrenia in given by intranasal. © 2024 Informa UK Limited, trading as Taylor & Francis Group.